Assessment of Human Milk Intake by Breastfed Infants Using Deuterium Oxide Dose-to-Mother Technique in “Tumbuh Kembang Anak” Cohort, Indonesia - E.K. Winarno; H. Winarno; S Susanto; T. Fajarwati; T. Thomas (Atom Indonesia, 2019)
Indonesia government has done the WHO recomendation that the infants should be exclusively breastfed for the first six months of life to achieve optimum growth, development and health. Nevertheless, the percentage of exclusive breastfed infants have not achieved the target yet and has not been scientifically quantified. The objective of the study is to measure the intake of human milk of Indonesian infants during first 6 months and to record the breastfeeding practices of mothers. Thirty healthy mother-infant pairs were recruited randomly for the cross-sectional study at “TumbuhKembangAnak” cohort in Bogor. Milk intake to the infant was measured using the deuterium oxide technique over 14 days. The interviews were done by members of team using the questionnaire to get the information on breastfeeding practice of respondents. The results showed that intake of human milk was 784 ± 117g.d-1 (mean ± SD), 787 ± 180 g.d-1 for infants 3 and 6 moths of age. It showed that the milk intake were not different between 3 and 6 months. The body composition of mothers, age, or parityhad no effects on milk intake of infants, education of mothers (3 months aged, P = 0.061, r = -0.097 and 6 months,  P = 0.616, r = -0.095), infants of3 months aged, P = 0.200, r = -0.290 and 6 months, P = -0.078, r = 0.684). Body mass index of mother (P < 0.05, r = 0.963) were correlated with the milk intake. About 53 % of the lactating mothers started breastfeeding within less than one hour of delivery. Breast-milk intake of the Indonesian infants were documented using deuterium oxide-to-the-mother technique.In the current study concluded that the exclusive breastfeeding practices with 30 pairs of mother-infant still shows that the conditions of exclusive breastfeeding practices have not been properly adhered to by mothers who deliver babies. It is recommended that "mother and baby health officer"  in Indonesia are increasingly promoting in order mothers in urban and rural areas to breastfeed exclusively for up to 6 months